Establishment of methods for rapid detection of Prymnesium parvum by recombinase polymerase amplification combined with a lateral flow dipstick - Luo, Ningjian; Huang, Hailong; Jiang, Haibo (Frontiers in Marine Science, 2022)
Prymnesium parvum is a toxic algal bloom (HAB)-forming species. The toxicity of this alga is a result of a collection of compounds known as prymnesins. Prymnesins exert harmful effects upon fish, shellfish, and mollusks, causing huge economic losses. In the present study, a new method was developed for the detection of P. parvum. The novel method utilizes isothermal amplification, known as recombinase polymerase amplification (RPA), in combination with lateral-flow dipstick (LFD). Herein, a set of primers and probes were designed for internal transcribed spacer (ITS) sequences, and a specific and sensitive RPA-LFD rapid detection method was established for P. parvum. Meanwhile, we verified its feasibility for the detection of environmental samples. It was demonstrated that the optimal amplification temperature and time for RPA were 39°C and 15 min. RPA/RPA-LFD was experimentally verified to be specific, demonstrating no cross-reaction with distinct control microalgae, and furthermore, the total time required for the RPA-LFD experiment was 20 min. Meanwhile, the detection limit for the genomic DNA of P. parvum was 1.5×10-1 pg/μL, and the detection limit for plasmids was 2.35 pg/μL. In addition, the results herein revealed that the RPA-LFD assay was 100 times more sensitive than PCR for detection of P. parvum. In conclusion, we developed an RPA-LFD that does not require precision instruments, and can be utilized for rapid on-site detection of P. parvum. In the future, the RPA-LFD can be considered for practical application for environmental detection of the toxic algal species.